2020
DOI: 10.1021/acs.accounts.0c00495
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated Olefin Metathesis: Catalyst Development, Synthesis, and Applications

Abstract: Conspectus The most important means for tuning and improving a catalyst’s properties is the delicate exchange of the ligand shell around the central metal atom. Perhaps for no other organometallic-catalyzed reaction is this statement more valid than for ruthenium-based olefin metathesis. Indeed, even the simple exchange of an oxygen atom for a sulfur atom in a chelated ruthenium benzylidene about a decade ago resulted in the development of extremely stable, photoactive catalysts. This Account pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 124 publications
0
45
0
Order By: Relevance
“…Using light to activate a latent catalyst has numerous advantages and offers control through judicious selection of irradiation energies to selectively, and at times orthogonally, guide synthetic schemes [6] . Moreover, having different photo‐latent catalysts that can be activated at different irradiation wavelengths is one of the motivations for exploring diverse ligand spheres, because changing the ligand sphere has been shown to affect photoactivation [7] . The most widely used anionic ligands in ruthenium benzylidenes are simple chlorides [8] .…”
Section: Figurementioning
confidence: 99%
“…Using light to activate a latent catalyst has numerous advantages and offers control through judicious selection of irradiation energies to selectively, and at times orthogonally, guide synthetic schemes [6] . Moreover, having different photo‐latent catalysts that can be activated at different irradiation wavelengths is one of the motivations for exploring diverse ligand spheres, because changing the ligand sphere has been shown to affect photoactivation [7] . The most widely used anionic ligands in ruthenium benzylidenes are simple chlorides [8] .…”
Section: Figurementioning
confidence: 99%
“…Although less widespread, ruthenium carbene complexes with such an overall coordination geometry are well known; they are commonly observed upon formal replacement of the ether oxygen of an archetype Grubbs-Hoveyda catalyst by heteroatoms exerting a stronger trans influence. [18][19][20][21][22][23] Provided that alkynes carrying appropriate such substituents are amenable to the light-driven gem hydrogenation, the resulting ruthenium carbene complexes could adopt the desirable coordination geometry, which in turn might potentially improve the outcome of the reaction in terms of selectivity, efficiency and yield.…”
mentioning
confidence: 99%
“…[84] The comparative study of metathesis reactions catalyzed by cAAC and NHC stabilized ruthenium complexes by Kaczanowska et al shows that the efficiency and selectivity arehighly dependent on the types of carbenes. [85] It has also been shown that the cAAC stabilized ruthenium-based complexes can be employed in light-activated [86] and amine-assisted olefin metathesis. [87] cAAC stabilized lanthanoids have also been reported that show catalytic properties.…”
Section: Caac-stabilized Metal Complexes In Organic Catalysismentioning
confidence: 99%